EKSPLORASI MINAT BAKAT ANAK USIA DINI MELALUI KEGIATAN INTERAKTIF PEMROGRAMAN VISUAL MENGGUNAKAN SCRATCH-JR - Rahmawati, Endra; Arianto, Muhammad Firdhi; Pitaloka, Diaz; Perdana, Muhammad Frizzy Alfarizzy (Universitas Mataram, 2025)
In the Industrial Revolution 4.0 Era, there is a great need for quality human resources who at least have critical thinking, problem solving, and creativity skills. To achieve this, grouping is needed to determine the interests and talents of early childhood students starting from the Kindergarten (TK) level. Exploring the interests and talents of early childhood can be a strategic approach to developing students' potential in the field of information technology. This activity can explore knowledge through creative visual programming activities using ScratchJr. ScratchJr is a visual programming application designed for children aged 5-7 years which is open source. This exploration activity method is packaged in the form of training and presentations which are divided into three stages, namely the Preparation Stage, Implementation, and Final Evaluation. The preparation stage begins with a survey and observation by coming directly to the school to find out what needs and challenges are faced by the teachers at the school in introducing the use of visual programming for students at the Kindergarten level. Then continued by compiling a training module that serves as a guide for participants, especially teachers, so that they can help their students learn Scratch Jr. In addition, there is an evaluation instrument to measure participants' understanding before and after the training ends, and there is an overall participant satisfaction value. The final evaluation results showed that 80.4% of participants were able to accept and utilize the ScratchJr application in creative visual programming activities such as character creation and animation. The use of ScratchJr in student collaborative activities can also provide social skills and develop children's holistic growth, but still accompanied by the student's Supervising Teacher.